Application of Mathematical-Cartographic Modeling for comprehensive landslide hazard assessment using the Analytic Hierarchy Process in the territory of the city of Saratov - Danilov, Vladimir Anatolievich; Morozova, Valeria A.; Moiseev, Denis S. (Известия Саратовского университета. Новая серия: Серия Науки о Земле)
The city of Saratov is subject to landslide processes, which occupy a significant part of its territory. Anthropogenic factors, such as irrational use of land, increasethe activation of landslide oftheterritory. The article considers naturalfactors as an aggregate influencing landslide formation on the territory of Saratov city and evaluates them. Application of Analytic Hierarchy Process (AHP) method in combination with GIS technologies allowed to reveal correlation dependencies between natural and anthropogenic factors influencing the occurrence and activation of landslides. Weighting coefficients of risk factors helped to assess the vulnerability of different parts of the city. One of the main research methods wasthe use of statistical algorithms andmethods ofmathematical and cartographicmodelingto create an integralmap oftheterritory’s resistance to landslide processes. The obtained data are important for planning of urban areas and development of landslide prevention measures. The created database can be used for systematic monitoring and accumulation of data on exogenous processes.